Praktik Baik Menulis kata Nama Hewan pada Siswa Kelas I SD Menggunakan Metode STAR dengan Media Sticky Note - Al Sidarto, Estiyowati; Daroe Iswatiningsih; Riska Kurnia (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to: (1) describe best practices in teaching students to write the names of animals using the STAR method with sticky notes, and (2) describe the success of improving first-grade elementary school students’ ability to write the names of animals. This study employed a mixed-methods approach that combined qualitative and quantitative methods. The research subjects were 29 first-grade students at SDN Madyopuro 3. The research data consisted of documents of students’ animal name writing performance, participatory observation, and interviews. The research results revealed two main findings. First, the process of best practices in writing animal names began with the teacher’s preparatory steps, followed by the application of the STAR method (Situation, Challenge, Action, Reflection). Second, there was an improvement in the success rate of writing animal names. Quantitatively, the percentage of student mastery increased from 51.7% to 86.2%. Qualitatively, it was described narratively that the students showed high enthusiasm. In conclusion, the STAR method was successfully implemented as a best practice in teaching students to write animal names.